Meta-Analysis: Application of Health Belief Model in Encouraging Preventive Behavior of Self-Care for Hypertensive Patients - Gusti Fathoni Firmansyah; Husna Arwa Salsabil (Journal of Health Promotion and Behavior, 2022)
Background: Hypertension is one of the most critical public health problems and has affected more than 1.2 billion people worldwide. Risk factors for hypertension can be divided into two, namely factors that cannot be controlled (such as gender, genetics and age) and those that can be controlled such as obesity, excess BMI, smoking, and excessive salt and fat consumption. Hypertension prevalence in age groups productive tends to increase from year to year, especially in the elderly group which reaches 63.22%. This study aimed to investigate behavior change and prevention of hypertension is the Health Belief Model (HBM).Subjects and Method: This article was compiled with a systematic review and meta-analysis study. This study uses the PICO Model as follows Population: Hypertension patients. Intervention: high self-efficacy and perceived susceptibility. Comparison: low self-efficacy and perceived susceptibility. Outcome: behavior change. The meta-analysis study was conducted by searching for articles from databases in electronic form including Google Scholar, PubMed, and Scopus. The keywords used are "hypertension" AND "health belief model (OR self efficacy OR perceived susceptibility)" AND "change behavior". The inclusion criteria for this study were full articles using a cross-sectional study, with the publication year 2012-2022. Analysis of articles in this study using RevMan 5.3 . software.Results: A total of 10 articles reviewed in the meta-analysis showed that perceived susceptibility influenced behavioral changes in hypertensive patients (aOR= 2.16; 95% CI= 1.59 to 2.53; p<0.001) and self-efficacy also influenced behavioral changes in hypertensive patients (aOR= 1.37; 95% CI= 1.06 to 1.76; p= 0.020).Conclusion: perceptions of vulnerability and self-efficacy affect behavior changes in hypertensive patients.Keywords: hypertension, health belief model, self efficacy, perceived susceptibility.Correspondence:Gusti Fathoni Firmansyah. Faculity of Dentistry, Universitas Gadjah Mada. Jl. Bulaksumur, Caturtunggal, Depok, Sleman, Yogyakarta 55281. Email: fathonifirmansyah@student.uns.ac.id. Mobile: +62 812-3710-7609.Journal of Health Promotion and Behavior (2022), 07(02): 108-118DOI: https://doi.org/10.26911/thejhpb.2021.07.02.03